Pengaruh Viral Marketring, Kekuatan Logo, Keputusan Pembelian Terhadap Keputusan Pembelian ( Studi KasusPada Outlet Mixue Di Ayani Kota Purwodadi ) - Siti Nurhidayah; winarsih (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2026)
Background & Purpose: The rapid expansion of Mixue is driven by a blend of effective digital marketing strategies, including viral marketing, brand logo strength, and product quality on social media. This raises questions about which factor most dominantly influences consumer purchasing decisions. Therefore, this study aims to comprehensively examine the impact of these three factors on consumer purchase decisions for Mixue products. A case study will be conducted in Purwodadi, which represents Mixue's success in penetrating small-town markets, and is expected to provide strategic insights for the F&B industry. Method: This study adopts a quantitative approach to analyze the influence of viral marketing (X1), logo strength (X2), and product quality (X3) on purchasing decisions (Y) among Mixue consumers in Purwodadi. The target population includes all Mixue ice cream buyers on Jl. A. Yani, with a sample of 112 respondents selected through simple random sampling. Primary data was collected using an online questionnaire, while secondary data was sourced from literature reviews. Data analysis will be performed using SPSS 24, including tests for validity and reliability, classical assumptions (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, coefficient of determination  test, and partial t-test, to comprehensively examine the research hypotheses. Results: Based on the research findings, it was discovered that viral marketing, logo strength, and product quality all have a positive and significant influence on consumer purchasing decisions. This indicates that a viral marketing strategy, a strong and memorable logo, and superior product quality collectively act as the primary drivers for consumers to make a purchase. These three factors don't stand alone; instead, they are mutually supportive and play a crucial role in shaping consumer behavior in the marketplace. Conclusion: This study concludes that viral marketing, logo strength, and product quality are crucial strategies for boosting consumer purchasing decisions. In the case of the Mixue outlet, all three of these aspects were found to significantly drive consumer interest and trust, ultimately influencing their decision to buy. Suggestion: Based on these findings, it is recommended that Mixue outlets maintain consistent product quality to build customer trust and loyalty. In addition, viral marketing strategies must be enhanced through creative content and collaboration with influencers to maintain consumer interest. Finally, the power of the logo and mascot “Snow King” needs to be continuously optimized in every promotional medium for the brand to make it easier for the brand to be more recognizable. By implementing this strategy, Mixue is expected to strengthen its position in the market and continue to increase purchasing decisions from consumers. Keywords: Viral Marketing, Logo Strength, Product Quality, Purchasing Decisions.